(untitled) (Plant Tissue Culture and Biotechnology, 2026)
This study aimed to optimize in vitro regeneration techniques and cytological characterization for medicinally potential plant Hemidesmus indicus. The shoot apices and nodal segments of field grown plants directly differentiated into multiple shoots buds (MSBs) when cultured on MS medium supplemented with different combinations of PGR’s. Shoot apices produced the highest number of MSBs (6.15 ± 0.14) per explant along with simultaneous development of green compact callus at the base when cultured on MS medium augmented with 2.0 mg/l BAP + 1.0 mg/l NAA. The synergistic effect of 1.0 mg/l BAP and 1.0 mg/NAA on MS medium produced the highest no. of MSBs (8.51 ± 0.16) per nodal explant. The leaf segments (91%) gave response to white friable calli in MS + 1.0 mg/1 2,4-D + 1.0 mg/l BAP. The calli further differentiated into MSBs showed indirect organogenesis. The elongated shoot buds were individually grown on rooting media. Maximum (8.17 ± 0.13) numbers of roots per micro shoots with the highest length (5.22 ± 0.03 cm) took place in ½MS + 1.0 mg/l IBA + 1.0 mg/l IAA medium. Well rooted plantlets were finally hardened to earthen pots with 88% survival rate. Comparative cytological analysis between in vivo and in vitro raised plants revealed 22 chromosomes in each somatic cell. The karyotypic formula for in vivo grown plants was 2Lsm + 6Msm + 6Mm + 8Sm whereas that of the in vitro plants was 2Lsm + 4Msm + 4Mm + 12Sm. Plant Tissue Cult. & Biotech. 36(1): 221-236, 2026 (June)